Faktor yang berhubungan dengan kejadian perdarahan post partum pada ibu bersalin - Anggraini, Novita Dwi; Fuziah, Nur Alfi; Kristianingsih, Ani; Sanjaya, Riona (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Postpartum hemorrhage is the loss of more than 500 cc of blood during or after birth. According to the results of the pre-survey conducted by researchers at RSUD Dr. H. Abdul Moelok of Lampung Province found that the number of deliveries with bleeding in 2019 was 78 (7.1 percent) cases of 1098 deliveries. The purpose of this research is to determine whether the factors related on the incidence of postpartum hemorrhage in Dr. H. Abdul Moeloek Lampung Province. The design used in this study is quantitative by using a Case-Control design. The population in this study were all postpartum mothers in 2019 at Dr. H. Abdul Moeloek Lampung Province. The sample used was maternity mothers who experienced bleeding and maternity mothers who did not experience bleeding that is with a ratio of 1: 1 so that the total sample was 156 people. Bivariate analysis in this study used the Chi-Square Test. The results of this study were obtained p-value less than 0.05 which is 0.007 which means there is a relationship between age and the incidence of postpartum hemorrhage, a p-value less than 0.05 which is 0.022 which means there is a relationship between parity and postpartum hemorrhage event, a p-value less than 0,05, which is 0.001, which means there is a relationship between old parturition and postpartum hemorrhage. For RSUD Dr. H Abdul Moeloek of Lampung Province to health workers and related parties in order to provide information to the public about postpartum hemorrhage as well as factors related to postpartum hemorrhage that is expected by the public to understand so as to reduce the number of postpartum hemorrhage events.